Role of Anatomy in Interns and Post-graduate Courses in Clinical Postings and Clinical Subjects - Makaju, Sarbada; Chaudhary, Sonam; Rai, Chandra Kala; Neupane, Bhima; Shrestha, Prashant (Journal of College of Medical Sciences-Nepal, 2025)
Background Anatomy serves as a fundamental pillar of medical education particularly during the first two years when the students are introduced to the basic sciences. A step-by-step approach to learning anatomy helps in building a strong foundation for clinical approaches. A comprehensive understanding of anatomical structures is essential for accurate diagnosis, surgical precision, physical examination, and overall clinical competence. Going through its critical role, this study aimed to assess the importance of anatomy, particularly the cadaveric dissection in clinical practice among medical graduates. Methods A descriptive, cross-sectional study was conducted among 180 medical graduates from 28/11/2024-28/02/2025. Ethical approval was obtained from the Institutional Review Committee, Kathmandu Medical College and Teaching Hospital (Ref. No. KMC-IRC 16102024/13). Convenience sampling was used and data were collected through a structured questionnaire-based survey. Statistical analysis was performed using SPSS version 16. Results Out of 180 participants, clinicians represented the largest group (36%), followed by house officers (27%), interns (24%), and residents (13%). A significant majority (87.8%) agreed that cadaveric dissection played an important role in developing sufficient clinical knowledge, skills, and confidence. Among interns, 23.3% moderately acknowledged anatomy as a core element in daily clinical decision-making. A notable 93.8% of clinicians emphasized the value of cadaveric exposure in enhancing clinical competency. Conclusions The cadaveric dissection remains a vital educational tool, bridging the gap between theoretical knowledge and practical application. The continues exposure to cadaveric in anatomy during clinical training enhances surgical and diagnostic skills ultimately contributing to improved patient safety and care outcomes.